BIS-MPA DENDRIMERS AS A PLATFORM FOR MOLECULAR IMAGING APPLICATIONS - Sadowski, Lukas (My University, 2016)
The objective of this research was to develop and validate new macromolecular imaging agents to detect and characterize malignant tumours. Using well-defined, highly branched macromolecules called dendrimers as the structural scaffold, efficient functionalization of the periphery was demonstrated using “click” chemistry in order to prepare multivalent imaging probes. Furthermore, a transmetalation was demonstrated to displace chelated copper with technetium, enabling “click” reactions to be performed in the presence of the dipicolylamine (DPA), a ligand known to chelate many metals. The dendritic scaffold was functionalized with either hydrophobic or hydrophilic targeting vectors. The hydrophobic ligand, an acyloxymethyl ketone targeting the overexpression of cathepsin B exhibited poor in vitro affinity when coupled to either G1 or G2 dendrimers, despite the use of various linkers. A glu-urea-lys dipeptide, representing a hydrophilic prostate specific membrane antigen targeting vector, demonstrated excellent affinity in vitro. The lead compound, a G2 dendrimer bearing four PSMA targeting vectors attached via an alkyl spacer was further investigated in vitro and in vivo. Unfortunately, poor tumor uptake was observed and the compound was hypothesized to hydrolyze readily (<15min), based on the in vitro plasma stability data. To rectify the aforementioned problem, non neo-pentyl esters were replaced with either carbamate or ether linkages. In vitro plasma stability analysis of the analogous compounds demonstrated increased stability. In particular, the ether analogue was found to be most stable, with minimal degradation observed after 4 hours.
Keywords: Bis-MPA, Dendrimer, Molecular Imaging, Technetium, Click Chemistry, Cathepsin B, PSMA